Metabolomic signatures of extreme old age: findings from the New England Centenarian Study - Stefano Monti; Michael S. Lustgarten; Ziwei Huang; Zeyuan Song; Mengze Li; Dylan Ellis; Qu Tian; Luigi Ferrucci; Noa Rappaport; Stacy L. Andersen; Thomas P. Perls; Paola Sebastiani (GeroScience, 2026)

Whole blood transcriptional signatures of age and survival identified in long life family and integrative longevity omics studies - Mengze Li; Zeyuan Song; Eric Reed; Tanya T. Karagiannis; Stacy Andersen; Michael Brent; Chase Mateusiak; Sandeep Acharya; Wooseok J. Jung; Shu Liao; Mary K. Wojczynski; Mary F. Feitosa; et al. (GeroScience, 2026)
Although aging is a universal event, some individuals are able to achieve extreme longevity. The Long-Life Family Study (LLFS) enrolls participants from families enriched with long-lived individuals, serves as a valuable dataset for studying ageing phenotypes and identify potential intervention targets. We analyzed the association between age at blood draw and 16,284 RNAseq-based blood transcriptomic data from 2,167 LLFS participants with ages ranging from 18 to 107, replicated the results in the Integrative Longevity Omics Study (ILO) dataset of 20,884 RNAseq-based blood transcriptomic data from 419 participants, with ages ranging from 60 to 108, and further compared our findings to a published reference aging signature. We identified 4,227 transcripts increasing and 4,044 transcripts decreasing with age, and enrichment analysis revealed age-related upregulation of inflammatory and senescence-related pathways, and downregulation of MYC and Wnt/β-catenin targets, among others. Further, a subset of transcripts showed age associations unique to the longevity-enriched cohorts (LLFS and ILO). We also identified 314 transcripts significantly associated with mortality risk and found that pro-survival gene sets included NK cell-mediated cytotoxicity and GPCR signaling. Finally, increased transcriptomic age predicted using transcriptomic clock was strongly associated with increased mortality. In summary, this study identified robust transcriptomic signatures of aging and mortality in a longevity-enriched population, highlighting key biological pathways such as immune modulation, inflammation, and senescence. Graphical abstract

Increased genetic protection against Alzheimer’s disease in centenarians - Harold Bae; Zeyuan Song; Amanat Ali; Takashi Sasaki; Niccolò Tesi; Hannah Lords; Anastasia Leshchyk; Yukiko Abe; Nobuyoshi Hirose; Yasumichi Arai; Nir Barzilai; Erica F. Weiss; et al. (GeroScience, 2025)

SNP rs6543176 is associated with extreme human longevity but increased risk for cancer - Anastasia Gurinovich; Zeyuan Song; Harold Bae; Anastasia Leshchyk; Mengze Li; Hannah Lords; Stacy L. Andersen; Marianne Nygaard; Kaare Christensen; E. Warwick Daw; Konstantin G. Arbeev; Michael R. Brent; et al. (GeroScience, 2025)

Cross-platform proteomics signatures of extreme old age - Eric R. Reed; Kevin B. Chandler; Prisma Lopez; Catherine E. Costello; Stacy L. Andersen; Thomas T. Perls; Mengze Li; Harold Bae; Mette Soerensen; Stefano Monti; Paola Sebastiani (GeroScience, 2024)

The relationship between 11 different polygenic longevity scores, parental lifespan, and disease diagnosis in the UK Biobank - Janith Don; Andrew J. Schork; Gwênlyn Glusman; Noa Rappaport; Steve R. Cummings; David Duggan; Anish Raju; Kajsa-Lotta Georgii Hellberg; Sophia Gunn; Stefano Monti; Thomas Perls; Jodi Lapidus; et al. (GeroScience, 2024)
Large-scale genome-wide association studies (GWAS) strongly suggest that most traits and diseases have a polygenic component. This observation has motivated the development of disease-specific “polygenic scores (PGS)” that are weighted sums of the effects of disease-associated variants identified from GWAS that correlate with an individual’s likelihood of expressing a specific phenotype. Although most GWAS have been pursued on disease traits, leading to the creation of refined “Polygenic Risk Scores” (PRS) that quantify risk to diseases, many GWAS have also been pursued on extreme human longevity, general fitness, health span, and other health-positive traits. These GWAS have discovered many genetic variants seemingly protective from disease and are often different from disease-associated variants (i.e., they are not just alternative alleles at disease-associated loci) and suggest that many health-positive traits also have a polygenic basis. This observation has led to an interest in “polygenic longevity scores (PLS)” that quantify the “risk” or genetic predisposition of an individual towards health. We derived 11 different PLS from 4 different available GWAS on lifespan and then investigated the properties of these PLS using data from the UK Biobank (UKB). Tests of association between the PLS and population structure, parental lifespan, and several cancerous and non-cancerous diseases, including death from COVID-19, were performed. Based on the results of our analyses, we argue that PLS are made up of variants not only robustly associated with parental lifespan, but that also contribute to the genetic architecture of disease susceptibility, morbidity, and mortality.

A metabolomic signature of the APOE2 allele - Paola Sebastiani; Zeyuan Song; Dylan Ellis; Qu Tian; Michaela Schwaiger-Haber; Ethan Stancliffe; Michael S. Lustgarten; Cory C. Funk; Priyanka Baloni; Cong-Hui Yao; Shakchhi Joshi; Megan M. Marron; et al. (GeroScience, 2023)

Distribution of 54 polygenic risk scores for common diseases in long lived individuals and their offspring - Sophia Gunn; Michael Wainberg; Zeyuan Song; Stacy Andersen; Robert Boudreau; Mary F. Feitosa; Qihua Tan; May E. Montasser; Jeffrey R. O’Connell; Nathan Stitziel; Nathan Price; Thomas Perls; et al. (GeroScience, 2022)

Correction to: Effect of longevity genetic variants on the molecular aging rate - Anastasia Gurinovich; Zeyuan Song; William Zhang; Anthony Federico; Stefano Monti; Stacy L. Andersen; Lori L. Jennings; David J. Glass; Nir Barzilai; Sofiya Millman; Thomas T. Perls; Paola Sebastiani (GeroScience, 2021)

Effect of longevity genetic variants on the molecular aging rate - Anastasia Gurinovich; Zeyuan Song; William Zhang; Anthony Federico; Stefano Monti; Stacy L. Andersen; Lori L. Jennings; David J. Glass; Nir Barzilai; Sofiya Millman; Thomas T. Perls; Paola Sebastiani (GeroScience, 2021)

Patterns of multi-domain cognitive aging in participants of the Long Life Family Study - Paola Sebastiani; Stacy L. Andersen; Benjamin Sweigart; Mengtian Du; Stephanie Cosentino; Bharat Thyagarajan; Kaare Christensen; Nicole Schupf; Thomas T Perls (GeroScience, 2020)

Heterogeneity of healthy aging: comparing long-lived families across five healthy aging phenotypes of blood pressure, memory, pulmonary function, grip strength, and metabolism - Megan M. Marron; Mary K. Wojczynski; Ryan L. Minster; Robert M. Boudreau; Paola Sebastiani; Stephanie Cosentino; Bharat Thyagarajan; Svetlana V. Ukraintseva; Nicole Schupf; Kaare Christensen; Mary Feitosa; Thomas Perls; et al. (GeroScience, 2019)

Improved tolerance toward fungal diseases in transgenic Cavendish banana (Musa spp. AAA group) cv. Grand Nain - Jane Vishnevetsky; Thomas L. White; Aaron J. Palmateer; Moshe Flaishman; Yuval Cohen; Yigal Elad; Margarita Velcheva; Uri Hanania; Nachman Sahar; Oded Dgani; Avihai Perl (Transgenic Research, 2011)

Combined NMR-observation of cold denaturation in supercooled water and heat denaturation enables accurate measurement of ΔC p of protein unfolding - Thomas Szyperski; Jeffrey L. Mills; Dieter Perl; Jochen Balbach (European Biophysics Journal, 2006)

The genetics of exceptional human longevity - Thomas Perls; Louis M. Kunkel; Annibale A. Puca (Journal of Molecular Neuroscience, 2002)